Analisis Zat Warna Rhodamin B dalam Lipstik yang Beredar di Pasar Setu Bekasi - Shafira Della Rosa; Sari Defi Okzelia (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
Rhodamine B is a synthetic dye that is commonly used in the textile industry, paper industry, and as a reagent. Rhodamine B can cause skin irritation, poisoning, and have carcinogenic effects. According to the regulation of the Head of BPOM RI No 18 (2015) concerning Technical Requirements for Cosmetic Ingredients, the use of Rhodamine B is prohibited in cosmetic preparations. From several studies that have been reported, Rhodamine B is still misused as dyes of various kinds of cosmetics such as lipstick. The purpose of this study is to identify and determine the levels of Rhodamine B in lipstick distributed in Setu Market, Bekasi. This research was carried out through the stages of sample collection and preparation, qualitative analysis using the Thin Layer Chromatography (TLC) method and quantitative analysis using UV-Vis spectrophotometric method. Samples were chosen by purposive sampling method which met criteria of red color, did not registered at BPOM and priced in the range of Rp. 5.000,00 -Rp. 15.000,00. Based on the result of TLC, out 2 of 5 samples contained Rhodamine B. Spectrophotometric quantitative analysis showed that the levels of Rhodamine B in the samples were 0.015% and 0.00067% respectively for sample C and sample E. From this research, it was known that Rhodamine B is still used as coloring agent in lipstick distributed in Setu Market, Bekasi.